2011
DOI: 10.1021/nl200126v
|View full text |Cite
|
Sign up to set email alerts
|

Shape Induced Symmetry in Self-Assembled Mesocrystals of Iron Oxide Nanocubes

Abstract: Grazing incidence small-angle scattering and electron microscopy have been used to show for the first time that nonspherical nanoparticles can assemble into highly ordered body-centered tetragonal mesocrystals. Energy models accounting for the directionality and magnitude of the van der Waals and dipolar interactions as a function of the degree of truncation of the nanocubes illustrated the importance of the directional dipolar forces for the formation of the initial nanocube clusters and the dominance of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
147
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(158 citation statements)
references
References 34 publications
9
147
2
Order By: Relevance
“…For example, (i) it has been demonstrated that T B can be easily increased by adding a surface layer of a hard material on a soft nanoparticle (soft/hard approach) [102,143,250], (ii) it has been shown that the coercivity (i.e., switching field) of hard nanoparticles is reduced when coupled to soft shells (hard/soft approach) [102,190], (iii) the possibility to form selfassembled arrays of core/shell nanoparticles [92][93][94]99,102,103,122,190,263,406] or (iv) possible graded anisotropy in core/shell nanoparticles [105]. Nevertheless, other critical features like large, defect free, self-assemblies of hard-soft core/shell nanoparticles (i.e., in the same range as the ones shown for single phase magnetic nanoparticles [407]) have not yet been demonstrated. In fact, although some types of inorganic core/shell nanoparticles have been shown to form well-ordered arrays [21], since as the shell is grown on the core the overall morphology can slightly deteriorate, consequently the self-assembly becomes increasingly difficult, as demonstrated in Fig.…”
Section: Recording Mediamentioning
confidence: 99%
“…For example, (i) it has been demonstrated that T B can be easily increased by adding a surface layer of a hard material on a soft nanoparticle (soft/hard approach) [102,143,250], (ii) it has been shown that the coercivity (i.e., switching field) of hard nanoparticles is reduced when coupled to soft shells (hard/soft approach) [102,190], (iii) the possibility to form selfassembled arrays of core/shell nanoparticles [92][93][94]99,102,103,122,190,263,406] or (iv) possible graded anisotropy in core/shell nanoparticles [105]. Nevertheless, other critical features like large, defect free, self-assemblies of hard-soft core/shell nanoparticles (i.e., in the same range as the ones shown for single phase magnetic nanoparticles [407]) have not yet been demonstrated. In fact, although some types of inorganic core/shell nanoparticles have been shown to form well-ordered arrays [21], since as the shell is grown on the core the overall morphology can slightly deteriorate, consequently the self-assembly becomes increasingly difficult, as demonstrated in Fig.…”
Section: Recording Mediamentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19] There are examples of mesocrystals ranging from biominerals to functional materials. [12] Mesocrystals are usually obtained by a self-assembly process of colloidal nanocrystals that are crystallographically oriented by surfactants and polymers in a superstructure and are usually solid materials.…”
Section: Introductionmentioning
confidence: 99%
“…[12] Mesocrystals are usually obtained by a self-assembly process of colloidal nanocrystals that are crystallographically oriented by surfactants and polymers in a superstructure and are usually solid materials. [12][13][14][15][16][17][18] Building blocks in these nonclassical crystals are usually nanomaterials with well-defined shape and size. [14] The synthesis of mesocrystals is carried out through a series of chemical reactions to form nanoparticles and self-assembly processes using organic directing agents and bottom-up approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, it seems more likely that the scattering maxima can be associated with the formation of a distorted (111)-oriented face-centered cubic mesophase. [47][48][49] Both of these structures are common in KLE-templated inorganics. [50][51][52] The degree of order is not as high as in other polymer-templated non-silicate thin films 32,34,42,53,54 -the vast majority are binary transition metal oxides -but the material studied in this work is rather complex from a chemical point of view in that three different sol-gel precursors were used in the synthesis.…”
Section: Resultsmentioning
confidence: 99%